الظواهر النحوية والصرفية في ديوان الرياض للشاعر النيجيري عيسى ألبي أبى بكر - Abdullahi Sulaiman Qudus
This research aims to study the Phenomena of Arabic Grammar and Morphology in the book, “Deewan al-Riyadh” written by the Nigerian poet, Issa Alabi Abu Bakr. The research problem is that the researchers who have previously conducted their studies on this book concentrated only on the rhetorical and literal aspects without considering the aspects of Arabic Grammar and Morphology, where as this Nigerian poet mentioned above is well-acquainted with the Arabic Grammar doctrines. Therefore, this research aims to analyze the Grammatical and Morphological phenomena in the book entitled, “Deewan al-Riyadh”, and explain the extent to which the poet agrees (in his work) with the doctrines of Arabic Grammar and Morphology. The researcher adopts in this studies descriptive and analytic approaches to study the eulogistic and congratulatory verses contained by this poetry book which comprises 1048 verses. These verses are also analyzed grammatically and morphologically. At the end, the researcher came up with some findings the most important of which are: Issa Alabi Abu Bakr is one of the prominent Arabic poets whose fame pervades not only Nigeria but also West Africa as a whole. He is strongly influenced by the schools of Kufa and Basra but not fanatical to any particular school of thought. Rather, it is ascertained that he sometimes advocates the school of Basra scholars, while at other times, he inclines towards the school of Kuffa scholars on the issues that have to do with Arabic Grammar and Morphology. This stance is clarified by the researcher with reference to some instances in his poetry. Moreover, the Grammatical and morphological phenomena that are in the book, “Deewan al-Riyadh” can be summarized to the issue of precession, succession, ellipsis, and value. It is observed that the number of verses with grammatical phenomena reaches 55, while the phenomena of precession and succession are obvious in 30 occasions. The phenomena of omission and value appear in 25 occasions. The morphological phenomena which are found in 282 verses revolve around the forms of verb and noun. In conclusion, the study proves that the book contains more morphological phenomena than grammatical ones.